Analysis Of The Covid-19 Prevention Culture: A Sociodemographic Approach In University Students - Porras- Roque, María Soledad; Centella-Centeno, Daniel Martin; Valderrama-Rios, Olga Giovanna; Mamani-Encalada, Antonia Emiliana; Chávez-Vidalón, Auristela; Cuba-Sancho, Juana Matilde (Migration Letters, 2024)
In recent years, humanity has faced a pandemic caused by the SARS-CoV-2 virus, where the measures indicated by the world health organization (WHO) are necessary for the new social coexistence. The research had as objective; determine the relationship between the preventive culture of Covid-19 and the sociodemographic characteristics in university students of Tacna – 2021; with a quantitative descriptive-correlational approach. In the selection of the sample, stratified random sampling was applied, obtaining 629 students, who virtually developed the questionnaire "Sociodemographic Characteristics" 0.90 and the Likert-type questionnaire "Culture of Prevention" 0.93, obtaining excellent validity. and reliability of 0.97. Chi square was used for bivariate analysis. It is worth mentioning that the ethical principles of autonomy, beneficence, justice and non-maleficence were respected. Results; An adequate level of prevention culture prevails in the students and with respect to the sociodemographic characteristics that stand out are female sex, young life stage, type of SIS insurance, urban residence, economic income <750 soles and absence of work performance. Conclusion; There is a significant relationship between the preventive culture of university students and the following variables: sex p=0.000, health insurance p=0.01, economic income p=0.00, occupation p=0.00, type of housing p= 0.00, housing tenure p=0.000), means of transportation p=0.01, means of communication p=0.00, type of family 0.00, experience with a family member P=0.02, sociocultural influence p=0.01 and personality traits such as neurocyticism p=0.04, sensation seeking p=0.02, aggressiveness p=0.00.